Another Asia Rabindranath Tagore and Okakura Tenshin - Bharucha, Rustom 1953- (New Delhi Oxford University Press, 2006)
On the works and friendship between Rabindranath Tagore, 1861-1941, Bengali and English author and Kakuz?o Okakura, 1862-1913, Japanese author with special reference to the depiction of Asia, nationalism, and civilization in their works.
Keywords: Tagore, Rabindranath -- 1861-1941 -- Criticism and interpretation; Okakura, Kakuzo -- 1862-1913 -- Criticism and interpretation; Nationalism in literature; Civilization in literature; Asia -- In literature